Panel 3: Universality of Architectural Education (EAAE Annual Conference Proceedings, 2023)
The panel was moderated by Regina Loukotová, architect, teacher and the Rector of the first private international school of architecture ARCHIP (Architectural Institute in Prague) in the Czech Republic, that she founded in 2011. The panel was preceded with a lecture by Inaki Alday who stressed the mandate for architecture: to solve problems – starting with providing shelter; and understanding that the new challenges have grown in scale and are the product of previous practices. The universality of the education and practice in our fields relies today in our shared objectives – the impact in an urgent planetary transformation, tools that are design focused to solve issues without artificial boundaries and methods as well as a continuous and accountable innovation mindset.